2021
DOI: 10.3390/ijerph18137210
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and COVID-19 Stress and Association with Sociodemographic and Psychological Process Factors in Cases under Surveillance in a Frontline Worker Population in Borneo

Abstract: COVID-19 stress and fear of COVID-19 is an increasingly researched construct in the general population. However, its prevalence and association with sociodemographic factors and psychological process variables has not been explored in frontline workers under surveillance in a Bornean population. This study was a cross-sectional study using a sociodemographic questionnaire incorporating two specific epidemiological risk variables, namely specific questions about COVID-19 surveillance status (persons under inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…An increased work burden due to the pandemic was also associated with increased psychological distress [ 10 , 17 , 18 ]. HCWs who were unvaccinated [ 19 ], working long hours (>15 hours/day) [ 20 ], and those investigated as close contacts, irrespective of the results of COVID-19 tests [ 21 ], showed higher levels of psychological distress. Occupational differences, with nurses exhibiting higher rates of anxiety and depression compared to other HCWs, were documented in two systematic reviews and meta-analysis by Pappa et al [ 10 ] and Marvaldi et al [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increased work burden due to the pandemic was also associated with increased psychological distress [ 10 , 17 , 18 ]. HCWs who were unvaccinated [ 19 ], working long hours (>15 hours/day) [ 20 ], and those investigated as close contacts, irrespective of the results of COVID-19 tests [ 21 ], showed higher levels of psychological distress. Occupational differences, with nurses exhibiting higher rates of anxiety and depression compared to other HCWs, were documented in two systematic reviews and meta-analysis by Pappa et al [ 10 ] and Marvaldi et al [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examining underlying psychological process variables, such as psychological mindedness, mindfulness, and psychological flexibility, can assist in the development of intervention initiatives. These variables have been chosen as they are reported as factors that may contribute to psychopathology in previous studies in a similar university population [9]. Psychological Mindedness (PM) is defined as an awareness of one's inner psychological processes and attitude towards these processes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a cross-sectional study, it was reported that 68.1% of students were worried about being infected by the COVID-19 virus. 7,8 In addition, other studies have shown that levels of fear, anxiety and depression related to COVI-19 are higher in persons who are students. 8,9 In our study, students were not sure of who was going to support them while in the clinical area as they were not certain of faculty members and clinical staff being able to supervise and teach them.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In addition, other studies have shown that levels of fear, anxiety and depression related to COVI-19 are higher in persons who are students. 8,9 In our study, students were not sure of who was going to support them while in the clinical area as they were not certain of faculty members and clinical staff being able to supervise and teach them. This was because the COVID-19 pandemic had forced the hospital management to reduce staffing levels as some were allocated to COVID-19 isolation centers, while faculty member visits were also uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation